EFEK MULTIPLIER ZAKAT TERHADAP PENDAPATAN DI PROVINSI DKI JAKARTA - M. Nur Rianto Al Arif (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2012)
The aim of this research is to analyse the multiplier effect of zakâh revenue in DKI Jakarta. A study case at Badan Amil Zakat, Infak, and Sadaqah (BAZIS) DKI Jakarta. Least square method is used to analyze the data. The coefficients will be used to calculate the multiplier effect of zakâh-revenue and it will be compared with the economy without zakah revenue. The results showed 2,522 multiplier effects of zakâh-revenue and 3.561 multiplier effect ofeconomic income without zakâh-revenue. This suggests that the management of zakat in BAZIS Jakarta still can have a significant influence on the economy.DOI: 10.15408/aiq.v4i1.2533